THE ANALYSIS OF EFFECTIVENESS OF LABORATORY USE TOWARD PHYSICS LEARNING RESULT - Ula, Sidratil; Safitri, Rini; Saminan, Saminan (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
Curriculum 2013 demands physics teachers to use laboratory in supporting the teaching and learning process at school, through laboratory students can apply the theory of physics concretely. The purpose of this study is to find out the effectiveness of laboratory in physics subject at senior high schools in Banda Aceh. This study used descriptive quantitative approach with surveying method. The population of this study is all senior high schools in Banda Aceh and the sample is 6 schools, 140 students and 6 teachers and laboratory chief, the sample was chosen using random stratified disproportionate sampling technique which was categorized based on the school accreditation. The technique used in data collection was questionnaire and observation sheet. The data analysis was done using descriptive technique with percentage formula. The result shows that the effectiveness of the use of laboratory toward physics subject learning at senior highschools in Banda Aceh is in the category less effective (56,78%). The indicator percentage in input is 59,23 and in process is 57,67 with â€œenoughâ€ category, while the output is 53,43 with â€œless effectiveâ€ category.